Sweden, Japan, and the Long Second World War 1931-1945 - Lottaz, Pascal (Routledge Studies in Second World War History, 2021)
We thank Ekman & Co AB and Gadelius Holding Ltd for their kind and generous support, making this research available online for free. Lottaz and Ottosson explore the intricate relationship between neutral Sweden and Imperial Japan during the latter's 15 years of warfare in Asia and in the Pacific. While Sweden's relationship with European Axis powers took place under the premise of existential security concerns, the case of Japan was altogether different. Japan never was a threat to Sweden, militarily or economically. Nevertheless, Stockholm maintained a close relationship with Tokyo until Japan's surrender in 1945. This book explores the reasons for that and therefore provides a study on the rationale and the value of neutrality in the Long Second World War. Sweden, Japan, and the Long Second World War is a valuable resource for scholars of the Second World War and of the history of neutrality.